Peningkatan Hasil Belajar pada Materi Offering Help Menggunakan Model Snowball Throwing - Endang Sugiharyanti (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2021)
This research is in the form of Classroom Action Research (CAR), because there are problems that the authors find in learning English, namely the percentage of students who get a score less than the Minimum Completeness Criteria which is set at 75. So that the author by carrying out CAR this is expected to improve the result of students learning who is given English learning in the Offering Help material using the Snowball Throwing model. CAR is conducted in class XII TKR A SMK Negeri 1 Ponjong. Researchers carry out research activities in 2 cycles, starting with planning, implementing, observing, reflecting, and improving. In the activity of each cycle the researcher did 2 meetings. The test results show that learning with the Snowball Throwing model runs better. This is evidenced by the percentage of student completeness values that have increased by 22%, shown in the first cycle an average of 71 and in the second cycle an average of 78, while the percentage of students who received an incomplete score decreased. At the end of the study, the mastery level of students classically increased from 68% to 90%.